Conhecimento Omágua/Kambeba e a educação em ciências: um estudo na escola municipal três unidos no rio Cuieiras/Baixo Rio Negro - Breves, Núbia do Socorro Pinto (2013)
The dissertation is a survey conducted in the indigenous community and United School District Three Three States - AUA Kambeba in Cuieiras / lower Rio Negro, which analyzes the contribution of knowledge that ethnicity for Science Education in the Amazon, considering how conducts practical teaching of Natural Sciences, a proposal for indigenous education, empowering its traditions, its territory and local sustainability. Aims to analyze the traditional knowledge of the people Omágua / Kambeba practices in the teaching and learning of natural sciences in the School Hall Three States - AUA Kambeba Cuieiras in Rio, and its articulation with the design of educational space in Science Education. While methodological procedure, we opted for a qualitative approach of historical reality, political and sociocultural Omágua / Kambeba, prioritizing knowledge of methodologies and indigenous conceptions of teaching and learning of Natural Sciences in different spaces of formal education, which today configures a perspective of intercultural education in the state of Amazonas. The findings suggest that people Omágua / Kambeba subsidizes their teaching-learning school in the early years of primary school, in the perspective of pedagogy project, focusing on interdisciplinary educational spaces, combining traditional knowledge with the official curriculum.